Research Status and Prospect of Cross-regional Medical Treatment in China Based on Bibliometric Analysis - LIU Chang, WANG Yufei (Zhongguo quanke yixue, 2024)
Background In the context of fragmented medical insurance and normalized population mobility, how to provide more convenient and efficient medical fee settlement services for patients with cross-regional medical treatment has become a hot issue of common concern in practice and theory. Objective To analyze the current situation, hotspots and evolutionary trends of research on the issue of cross-regional medical treatment in China, so as to provide a reference for the research on cross-regional medical treatment. Methods CNKI was searched for papers in the field of cross-regional medical treatment in China from inception to 2023-06-10. CiteSpace software was used to perform quantitative analyze of literature data in the field of cross-regional medical treatment and visual analysis of knowledge graph in terms of publication time, author, institution and keywords. Results A total of 590 papers were finally retrieved. The publication volume in the field of cross-regional medical treatment in China broke through the single digit for the first time in 2009 to 16, and exhibited a fluctuating trend in the following years. There were 57 core authors who published more than 3 articles, and the total number of published articles was 238, accounting for 40.34% of the total number of sample articles, with the author collaborative network density of 0.051. Most of the articles were published by universities, research institutes, medical institutions and local health insurance management departments. Institute of Medical Information Sciences Chinese Academy of Medical Sciences ranked first with 22 publications, followed by the School of International Pharmaceutical Business, China Pharmaceutical University with 9 publications, North China University of Science and Technology with 8 publications, Huashan Hospital affiliated to Fudan University with 6 publications, and Jiangxi University of Chinese Medicine with 6 publications. The collaborative network density among research institutions was only 0.001 6. Keyword frequency analysis showed 424 nodes and 1, 188 edges in the keyword network mapping, with a network density of 0.013 2, "cross-regional medical treatment""medical insurance""cross-provincial medical treatment" and "different settlement" occupied a central positions in the co-occurring keyword network. Keyword clustering timeline mapping analysis showed a total of nine clustering themes formed, including "different settlement" "medical insurance" "immediate reimbursement" "management" "New Rural Cooperative" "cross-provincial medical treatment" "satisfaction" "Yangtze River Delta" "hierarchical diagnosis and treatment". Conclusion The quality and depth of research in the field of cross-regional medical treatment in China are continuously improving. However, there are still deficiencies in research methodology, research content and collaborative network. It is necessary to focus on challenges and issues in the field of cross-regional medical treatment, promote the innovation of research methods, and continuously strengthen the communication and cooperation among scholars.